PENGARUH PROFITABILITAS, LIKUIDITAS, STRUKTUR AKTIVA DAN GROWTH OPPORTUNITY TERHADAP STRUKTUR MODAL - Dewi Anggita; Sugeng Priyanto (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to determine the effect of the variabels Profitability, Liquidity, Asset Structure and Growth Opportunity on Capital Structure in Properti and Real Estate Companies. The population used in this study are Properti and Real Estate Companies listed on the Indonesia Stock Exchange with a research observation period of 2017 – 2021. The sample selection used a purposive sampling method based on certain criteria that were adjusted to the objectives of the research problem. The number of samples used in this study as many as 15 of 80 companies. The data analysis technique used in this study is Multiple Linear Regression Analysis with the SPSS version 19 program tool. The results of this study indicate that Profitability and Liquidity have a negatif and significant effect on capital structure. Growth Opportunity has a positif and significant effect on the capital structure. Meanwhile, asset structure has no significant effect on capital structure.